Fast track - Garwood, Julie (Dutton, 2014)
"Family secrets and a hidden past-a woman's search to uncover the truth ignites danger and passion in the latest novel from #1 New York Times-bestselling author Julie Garwood. Cordelia Kane has always been a daddy's girl-her father raised her alone after her mother died in a car crash when Cordelia was just two years old. So when he has a serious heart attack, Cordelia is devastated, and the emotion is only intensified by the confusion she feels when he reveals the shocking truth about her mother. Cordelia can't suppress her curiosity about the woman who gave birth to her, and when she discovers the answers to her questions lie in Sydney, Australia, she travels there to get them. Hotel magnate Aiden Madison is Cordelia's best friend's older brother. He's oblivious to the fact that she's had a crush on him for years. When he gets railroaded into taking her along to Sydney on his company jet, he's unwittingly drawn into a volatile family drama. Aiden wants to help Cordelia get answers about her mother, but threats from her wealthy, high-powered family are quickly becoming dangerous. Sparks are flying between Cordelia and Aiden, but after multiple attempts are made on Cordelia's life, Aiden realizes he must put a stop to the madness before he loses the thing he values most"--